STRATEGY TO IMPROVE STUDENTS' CREATIVITY AND PUBLIC SPEAKING USING AUDIO VISUAL AND DIGITAL VIDIO METHODS IN HISTORY LEARNING - Rospiyanti Triningsih (Satmata: Journal of Historical Education Studies, 2024)
This research aims to find out the best solution to improve students' public speaking skills and creativity in history subjects. This research uses a literature study method using existing research sources. From the research results, whether history learning is successful or not is greatly influenced by student creativity and public speaking in class. To increase students' creativity and public speaking, teachers need interesting learning methods. The learning method that attracts high school/vocational school students' attention to history subjects is digital audio visual and video, making history learning boring, but on the contrary. Audio-visual and digital learning methods are good uses of technology by teachers in developing the field of education, especially in helping students develop creativity and improve public speaking skills. The use of digital audio-visual and video strategies in history learning to increase creativity and public speaking must be adjusted to the interests of students in each school.